2017
DOI: 10.1094/phyto-07-16-0251-r
|View full text |Cite
|
Sign up to set email alerts
|

CatB is Critical for Total Catalase Activity and Reduces Bactericidal Effects of Phenazine-1-Carboxylic Acid on Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola

Abstract: Rice bacterial leaf blight, caused by Xanthomonas oryzae pv. oryzae, and rice bacterial leaf streak, caused by X. oryzae pv. oryzicola, are major diseases of rice. Phenazine-1-carboxylic acid (PCA) is a natural product that is isolated from Pseudomonas spp. and is used to control many important rice diseases in China. We previously reported that PCA disturbs the redox balance, which results in the accumulation of reactive oxygen species in X. oryzae pv. oryzae. In this study, we found that PCA significantly up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…We also found that exogenous CAT dramatically reduced anti‐bacterial activity of PTL, and 100 U mL −1 of exogenous CAT almost fully abolished its anti‐bacterial effect, suggesting that ROS is critical in the bactericidal effect of PTL. This result is also similar to PCA . To further confirm the relationship between CAT and the bactericidal effect of PTL, we tested PTL sensitivity of CAT deletion mutants of Xoo , and found that PTL sensitivity of these mutants significantly increased compared with that of wild‐type Xoo strain.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We also found that exogenous CAT dramatically reduced anti‐bacterial activity of PTL, and 100 U mL −1 of exogenous CAT almost fully abolished its anti‐bacterial effect, suggesting that ROS is critical in the bactericidal effect of PTL. This result is also similar to PCA . To further confirm the relationship between CAT and the bactericidal effect of PTL, we tested PTL sensitivity of CAT deletion mutants of Xoo , and found that PTL sensitivity of these mutants significantly increased compared with that of wild‐type Xoo strain.…”
Section: Discussionsupporting
confidence: 73%
“…Xoo strains include ZJ173, ΔZ/ catB , ΔZ/ katE , and ΔZ/ srpA . ΔZ/ catB , ΔZ/ katE , and ΔZ/ srpA are CAT deletion mutants generated from wild‐type Xoo strain ZJ173 . Bacterial cells were grown at 28 °C in nutrient broth (NB) medium in conical flasks with shaking at 175 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with superoxide dismutase and glutathione peroxidase, catalase plays a vital role in the antioxidant systems that protect against the adverse effects of free radicals (Blackman and Hardham, 2008;Ighodaro and Akinloye, 2018). Many studies have confirmed that catalase is required for the growth, development, and pathogenesis of various organisms (Wysong et al, 1998;Schriner et al, 2005;Pan et al, 2017;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%